Antioxidant enzyme activities as biomarkers of Cu and Pb stress in Centella asiatica - Yap, Chee Kong; Tan, Wen Siang; Wong, Koe Wei; Ghim, Hock Ong; Wan, Hee Cheng; Nulit, Rosimah; Ibrahim, Mohd Hafiz; Chew, Weiyun; Edward Thomas, Franklin Berandah; Okamura, Hideo; Al-Mutairi, Khalid Awadh; Al-Shami, Salman Abdo; et al. (Multidisciplinary Digital Publishing Institute, 2021)
The present study investigated the antioxidant enzyme activities (AEA) of ascorbate peroxidase (APX), catalase (CAT), guaiacol peroxidase (GPX), and superoxide dismutase (SOD) as biomarkers of Cu and Pb stress by using Centella asiatica grown in an experimental hydroponic condition. The results showed (i) higher accumulations of Cu and Pb in the roots of C. asiatica than those in the leaves, (ii) synergistic effects of Cu and Pb stress at higher metal-level exposures, and (iii) Cu and Pb stress triggered the increment of APX, CAT, GPX, and SOD levels in both the leaves and roots of C. asiatica. The increment of four AEA indicated that C. asiatica underwent oxidative stress caused by the production of reactive oxygen species when the plant was exposed to Cu and Pb. In order to prevent damages caused by Cu and Pb stress, the AEA system was heightened in C. asiatica, in which APX, CAT, GPX, and SOD can be used as biomarkers of Pb and Cu stress in the plant.